The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.iecr.1c04719
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfur-Containing Porous Organic Polymer as a Nanotrap for Rapid Removal of Mercury(II) from Environmental Waters

Abstract: A novel porous organic polymer with thioetherfunctionalized succinimide (TS-POP) through radical copolymerization as a facile, metal-free, and cost-effective strategy for Hg 2+ removal from aqueous solution is presented. Fourier transform infrared (FT-IR) spectroscopy and powder X-ray diffraction (XRD) were used to confirm the structure, while morphology, porosity, and physicochemical properties were determined using scanning electron microscopy (SEM), N 2 adsorption/desorption isotherm, and thermogravimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It was hypothesised that the imidothiocarbonate linkage could act as a coordinating group. Indeed, previous studies have found S and N containing polymers to be effective at removal of Hg 2+ from aqueous solutions, with adsorption of Hg 2+ often attributed to simultaneous binding to S and N. 37–39 Similarly, polymeric Schiff bases have been found to form metal complexes, in particular with Cu 2+ . 40–46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hypothesised that the imidothiocarbonate linkage could act as a coordinating group. Indeed, previous studies have found S and N containing polymers to be effective at removal of Hg 2+ from aqueous solutions, with adsorption of Hg 2+ often attributed to simultaneous binding to S and N. 37–39 Similarly, polymeric Schiff bases have been found to form metal complexes, in particular with Cu 2+ . 40–46…”
Section: Resultsmentioning
confidence: 99%
“…to S and N. [37][38][39] Similarly, polymeric Schiff bases have been found to form metal complexes, in particular with Cu 2+ . [40][41][42][43][44][45][46] Two metal ions were considered, Cu 2+ and Co 3+ , which had been previously identified as toxic metals found in wastewater and which would allow colorimetric titration to monitor complexation.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…Porous organic polymers (POPs) have emerged as highly promising materials in the fields of energy and environment over the past decades. Their exceptional performance on adsorption and separation, catalysis, energy storage, and conversion has made them valuable for applications such as water treatment, adsorption and conversion of greenhouse gases, adsorption of metal ions, and membrane separation. These capabilities highlight the significant potential of POPs in addressing various challenges in the realms of energy and environmental sustainability. The characters and functions of POPs are tunable through the strategic design of functional monomers as well as polymerization techniques. …”
mentioning
confidence: 99%